Generation of BroÌˆnsted acidity in AlMCM-41 by sulphation for enhanced liquid phase tert-butylation of phenol - Ng, Eng Poh; Nur, Hadi; Wong, Ka Lun; Muhid, Mohd Nazlan Mohd; Hamdan, Halimaton (Elsevier B.V., 2007)

(untitled)
AlMCM-41 mesoporous molecular sieve modified by impregnation with sulphuric acid in toluene possesses only BroÌˆnsted acid sites. The catalyst exhibits a high catalytic activity for tert-butylation of phenol with high selectivity to 2,4-di-tert-butylphenol in liquid phase. 27Al MAS NMR study indicates that the modification of AlMCM-41 with sulphuric acid in toluene leaves only octahedrally coordinated Al species. The tetrahedrally coordinated Al species which exist before modification with sulphuric acid in toluene being dealuminated to form extraframework octahedrally coordinated Al species. The mesoporous structure of AlMCM-41 is retained after modification, but pore size decreases by ca. 3 AÌŠ by the modification. The active sites are postulated on the basis of XRD, FTIR, 27Al MAS NMR, TGA, BET analysis and FTIR-pyridine adsorption studies that -OSO3H bonded to octahedrally coordinated Al species.